Perkembangan Morfologi Guna Lahan di Kawasan Periphery Kota Makassar - Sitti Adliyani; Bambang Heryanto; Ihsan Ihsan (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
The existence of public services is a strong factor in development area centrifugally. One type of public services in Makassar Periphery Area is Hasanuddin University Educational District. Development of large district of education will be followed by increasing of resident and activity support amount that influence the developing built-up area. Development of the built-up area was analyzed by spatially, descriptive and binary regression methods. Factors affecting the development of the built-up area were the presence of attractive elements such as campus, infrastructure and facilities, strategic location, and the cheap land prices. The growth forms of the built-up area are grid and linear pattern with some buildings used for housing, government facilities, office facilities and educational facilities. Linear pattern lies through the street fanced by the buildings used as trade and service facilities. The impacts of built-up area development are the increasing of building density, kindship society, land value and building’s physical condition.